VD_FINDINFO Décision / 2013 / 681 vom 8. März 2013 - VD Tribunal cantonal (2013)
INDEMNITÉEN GÉNÉRAL, AVOCAT, TRIBUNAL FÉDÉRAL | 107 al. 2 LTF, 310 CPP (CH), 393 al. 1 let. a CPP (CH), 429 al. 1 let. a CPP (CH)